2020
DOI: 10.31186/j.agroindustri.10.2.118-128
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Topografi Lahan Dan Tinggi Pohon Dengan Kelelahan Pekerja Dan Produktivitas Pemanenan Kelapa Sawit

Abstract: The purpose of this research was to analyze the correlation between topography with fatigue of worker, height of tree with fatigue of worker, topography and height of tree with fatigue of worker and fatigue of worker with productivity of palm oil harvesting. The analytical method used in this research was the analysis of correlation and linear regression. Based on the results of this study concluded that there was a weak correlation (r = 0,214), but significant and in the same direction (positive) between topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…al. [6] found that the higher the topography of the ground surface (degree of slope) the higher the fatigue of workers. High worker fatigue eventually leads to low work productivity.…”
Section: Irhr St Wec St Irhr Work and Wec Workmentioning
confidence: 99%
“…al. [6] found that the higher the topography of the ground surface (degree of slope) the higher the fatigue of workers. High worker fatigue eventually leads to low work productivity.…”
Section: Irhr St Wec St Irhr Work and Wec Workmentioning
confidence: 99%
“…Pengelolaan perkebunan kelapa sawit yang tidak memperhatikan kelestarian lingkungan seperti menanam di lahan bertopografi miring akan berdampak buruk pada lingkungan (Visano et al, 2020). Kemiringan lahan turut mempengaruhi faktor sifat tanah dalam mendukung pertumbuhan dan peningkatan produksi kelapa sawit, termasuk mempengaruhi ketersediaan C-organik, dan ketersediaan unsur makro seperti N, P dan K, serta unsur mikro berupa unsur Mg (Harahap & Munir, 2022).…”
Section: Pendahuluanunclassified